Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 62308 by aliesam last updated on 19/Jun/19

Commented by maxmathsup by imad last updated on 20/Jun/19

x^2 −2x  +2 =0 →Δ^′  =1−2 =−1 =i^2  ⇒α =1+i  and β =1−i =α^−  ⇒  α^n  +β^n  =α^n  +(α^− )^n  =2 Re(α^n )    we have  α =(√2)e^((iπ)/4)  ⇒α^n  =((√2))^n  e^((inπ)/4)    ⇒Re(α^n ) =2^(n/2)  cos(((nπ)/4)) ⇒α^n  +β^n  =2^(1+(n/2))  cos(((nπ)/4)) = 2^((n+2)/2)  cos(((nπ)/4)).

x22x+2=0Δ=12=1=i2α=1+iandβ=1i=ααn+βn=αn+(α)n=2Re(αn)wehaveα=2eiπ4αn=(2)neinπ4Re(αn)=2n2cos(nπ4)αn+βn=21+n2cos(nπ4)=2n+22cos(nπ4).

Commented by aliesam last updated on 20/Jun/19

thank you sir

thankyousir

Answered by tanmay last updated on 19/Jun/19

(x−1)^2 +1=0  (x−1)^2 −i^2 =0  (x−1+i)(x−1−i)=0  α=1+i   β=1−i  α^n +β^n   =(1+i)^n +(1−i)^n   =[(√2) ((1/(√2))+i×(1/(√2)))]^n +[(√2) ((1/(√2))−i×(1/(√2)))]^n   =[(√2) (cos(π/4)+isin(π/4))]^n +[(√2) (cos(π/4)−isin(π/4))]^n   =[(√2) ×e^(i×(π/4)) ]^n +[(√2) ×e^(−i×(π/4)) ]^n   =(2)^(n/2) [e^(i×((nπ)/4)) +e^(−i×((nπ)/4)) ]  =2^(n/2) ×2cos(((nπ)/4))  =2^((n+2)/2) ×cos(((nπ)/4))

(x1)2+1=0(x1)2i2=0(x1+i)(x1i)=0α=1+iβ=1iαn+βn=(1+i)n+(1i)n=[2(12+i×12)]n+[2(12i×12)]n=[2(cosπ4+isinπ4)]n+[2(cosπ4isinπ4)]n=[2×ei×π4]n+[2×ei×π4]n=(2)n2[ei×nπ4+ei×nπ4]=2n2×2cos(nπ4)=2n+22×cos(nπ4)

Commented by aliesam last updated on 19/Jun/19

god bless you sir

godblessyousir

Commented by tanmay last updated on 19/Jun/19

blessings shower to all.

blessingsshowertoall.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com